hSMG-1 and ATM sequentially and independently regulate the G1 checkpoint during oxidative stress - Gehen, Sean C. (2008)
Genotoxic stress activates the phosphatidylinositol 3-kinase like kinases (PIKKs) that phosphorylate proteins involved in cell cycle arrest, DNA repair, and apoptosis. Previous work showed that the PIKK ataxia telangiectasia mutated (ATM) but not ATR (ATM and Rad3-related) phosphorylates p53 (Ser15) during hyperoxia, a model of prolonged oxidative stress and DNA damage. Here, we show hSMG-1 is responsible for the rapid and early phosphorylation of p53 (Ser15) and that ATM helps maintain phosphorylation after 24 hours. Despite reduced p53 phosphorylation and abundance in cells depleted of hSMG-1 or ATM, levels of the p53 target p21 were still elevated and the G1 checkpoint remained intact. Conditional over-expression of p21 in p53-deficient cells revealed that hyperoxia also stimulates wortmannin-sensitive degradation of p21. SiRNA depletion of hSMG-1 or ATM restored p21 stability and the G1 checkpoint during hyperoxia. These findings establish hSMG-1 as a proximal regulator of DNA damage signaling and reveal that the G1 checkpoint is tightly regulated during prolonged oxidative stress by both PIKK-dependent synthesis and proteolysis of p21.